Some Ethics of Work In Islam Compared to the Principles of The Human Relations and Work Ethics In The Civil Service Law In Saudi Arabia - Al Sharif, Raja Ben Yahya; Fadel, Fatima bint AbdulRakeeb (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to handle and discuss some ethics of work in Islam compared to the principles of the human relations and work ethics in the civil service law in Saudi Arabia. The study has applied the comparative descriptive methodology. The tool was represented in analysis for some documents and book references. The study comprises the introduction and three themes. The first theme included the Sharia lawful interpretations and commentaries on morals and ethics. The second theme covered the human relations and regulatory ethics and their characteristics while the third theme covered the business code of ethics in the Civil Service Law in Saudi Arabia. The study results have shown that the Islam has exceeded the contemporary schools in the field of human relations and code of ethics. In view of the results, group of recommendations and proposals have been established to refer to the heavenly glorious book and the holy prophet’s traditions (Sunna), to get proud of and adhere to the Quran teachings.